Dual Effect of Chrysanthemum indicum Extract to Stimulate Osteoblast Differentiation and Inhibit Osteoclast Formation and Resorption In Vitro. (27th October 2014) - Baek, Jong Min; Kim, Ju-Young; Cheon, Yoon-Hee; Park, Sun-Hyang; Ahn, Sung-Jun; Yoon, Kwon-Ha; Oh, Jaemin; Lee, Myeung Su
Abstract : The risk of bone-related diseases increases due to the imbalance between bone resorption and bone formation by osteoclasts and osteoblasts, respectively. The goal in the development of antiosteoporotic treatments is an agent that will improve bone through simultaneous osteoblast stimulation and osteoclast inhibition without undesirable side effects. To achieve this goal, numerous studies have been performed to identify novel approaches using natural oriental herbs to treat bone metabolic diseases. In the present study, we investigated the effect of Chrysanthemum indicum extract (CIE) on the differentiation of osteoclastic and osteoblastic cells. CIE inhibited the formation of TRAP-positive mature osteoclasts and of filamentous-actin rings and disrupted the bone-resorbing activity of mature osteoclasts in a dose-dependent manner. CIE strongly inhibited Akt, GSK3 β, and I κ B phosphorylation in RANKL-stimulated bone marrow macrophages and did not show any effects on MAP kinases, including p38, ERK, and JNK. Interestingly, CIE also enhanced primary osteoblast differentiation via upregulation of the expression of alkaline phosphatase and the level of extracellular calcium concentrations during the early and terminal stages of differentiation, respectively. Our results revealed that CIE could have a potential therapeutic role in bone-related disorders through its dual effects on osteoclast and osteoblast differentiation.